La critique de paysage peut-elle être scientifique ? - Catherine Chomarat-Ruiz (Projets de Paysage)
Focusing on the scientific character of the landscape criticism, this article distinguishes this practice from the landscaping hermeneutics and expertise : it compares it to art criticism and brings it back to the critical interpretation of a project. Then it addresses the issue of values attributed to landscape in order to emphasize their contradictory, arbitrary and relative natures. It highlights the fact that the epistemological issue faced by this type of criticism engages the ethical question of landscape transmission. Based on this, the article proposes solutions brought by the production of criteria, on which values are based on, a hierarchy of values or a multidisciplinary perspective. Incomplete, these solutions enable us to express the hypothesis of a new landscape science which could support the criticism. This article reckons the advent of a meta-criticism of landscape and the gain of scientificity and morality which it would represent.